Disseminated Tuberculosis with Testes Involvement: An Intriguing Case Report - Arnab Kundu; Ramanuj Mukherjee; Ayan Parichha; Gouri Mukhopadhyay (University Library System, University of Pittsburgh, 2024)
Background: Disseminated tuberculosis (TB) is the presence of two or more noncontiguous sites resulting from hematogenous dissemination of Mycobacterium tuberculosis. We report a case of disseminated TB with testicular involvement. Case: A 21-year-old male patient presented to the outpatient department with bilateral testicular enlargement and tenderness for last six months. It was suspected to be a case of epididymo-orchitis and empirical antimicrobial therapy was initiated. However, ultrasonography findings were inconsistent with epididymo-orchitis. Two weeks later the patient again presented with increased nodularity in the right testes. Non-seminomatous germ cell tumor was suspected. However, tumor markers came back normal. Magnetic resonance imaging revealed enlarged lymph nodes in the right inguinal and retroperitoneal region raising a suspicion of testicular lymphoma. Positron emission tomography with computed tomography showed multiple lymphadenopathies. Histopathology of the left axillary lymph node finally confirmed the diagnosis to be tuberculosis. No drug resistance were found and the patient responded well to anti-tubercular drugs. Conclusion: Diagnosing disseminated TB is difficult as it mimics conditions, such as infarction, cancer, torsion, etc. Attention to small details is necessary. We faced a similar situation in our patient. The patient went through a myriad of tests before finally being diagnosed with TB. Histopathological study was able to get it whereas cytology could not. Similar and totally opposite cases were found in the literature. This highlights the difficulty and importance of these type of cases.